2020
DOI: 10.1055/s-0040-1707315
|View full text |Cite
|
Sign up to set email alerts
|

Straightforward Synthesis of 3-Selenocyanato-Substituted Chromones through Electrophilic Selenocyanation of Enaminones under Grinding Conditions

Abstract: A metal- and oxidant-free method for preparing 3-selenocyanato-substituted chromones from 2-hydroxyphenyl enaminones by using a newly developed electrophilic selenocyanating reagent is reported­. A series of 3-selenocyanato- or 3-thiocyanato-substituted chromones, as well as 3-selenocyanato- or 3-thiocyanato-substituted quinolinones was obtained in good to excellent yields under grinding reaction conditions. The generality and utility of this approach were demonstrated by a scale-up reaction and transformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…More recently, Xiao, Ren and co-workers reported a grinding-mediated electrophilic cyclization of 2-substituted enaminones 83 in the presence of N -selenocyanophthalimide 84 as a selenocyanating reagent to afford 3-selenocianato-substituted chromones 85 [ 100 ]. The reactions were conducted in an agate mortar in the absence of solvent, and after grinding for just 20 min at room temperature, the desired products 85 were obtained in moderate to excellent yields, presenting a good substrate tolerance.…”
Section: Application Of Non-conventional Energy Sources In Organosele...mentioning
confidence: 99%
“…More recently, Xiao, Ren and co-workers reported a grinding-mediated electrophilic cyclization of 2-substituted enaminones 83 in the presence of N -selenocyanophthalimide 84 as a selenocyanating reagent to afford 3-selenocianato-substituted chromones 85 [ 100 ]. The reactions were conducted in an agate mortar in the absence of solvent, and after grinding for just 20 min at room temperature, the desired products 85 were obtained in moderate to excellent yields, presenting a good substrate tolerance.…”
Section: Application Of Non-conventional Energy Sources In Organosele...mentioning
confidence: 99%
“…When 1‐acetyl‐2‐naphthol enaminone ( 58 l ) and 3,5‐dichloro‐2‐hydroxyphenyl enaminone ( 58 m ) were reacted under these reaction conditions, the resulting selenocyanates ( 60 l and 60 m ) were achieved in good yields (Scheme 31a). The selenocyanation was also accomplished well on various N ‐protected 2‐aminophenyl enaminones ( 61 a – 61 d ) with different substituents with the newly produced selenocyanatophthalimide reagent ( 59 ), producing the corresponding selenocyanated quinolinones ( 62 a – 62 d ) in good to moderate yields (Scheme 31b) [28] . The author suggested that the imine intermediate 58 A be provided through an electrophilic selenocyanation process using selenocyanating agent 59 .…”
Section: Synthetic Approaches Of Organo‐selenocyanates (Oscs)mentioning
confidence: 99%
“…Huang and coworkers used a newly produced electrophilic selenocyanato‐phthalimide reagent 59 to create an effective method for the synthesis of 3‐selenocyanato‐substituted chromones 60 and quinolinones 62 from various enaminone derivatives ( 58 or 61 ) in good to high yields under grinding conditions [28] . The reaction exhibited remarkable functional group adaptability regardless of the nature (electron accepting or ‐releasing groups) as well as at any position of the substituents on the aromatic part of the 2‐hydroxyphenyl enaminone derivatives ( 58 a – 58 k ).…”
Section: Synthetic Approaches Of Organo‐selenocyanates (Oscs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently,X iao, Ren, Huang, and co-workers reported the synthesis of the electrophilic selenocyanate source XIII [35] from N-chlorophthalimide and silver selenocyanate in 87 %y ield (Scheme 28). [36] The selenocyanatophthalimide reagent XIII was then appliedt ot he selenocyanation of enaminone derivatives 85 or 87,w hich after cyclization led to the corresponding 3-selenocyanato-substituted chromones 86 and quinolinones 88.…”
Section: The N-selenocyanatophthalimide Sourcementioning
confidence: 99%